Reach for greatness personalizable education for all children - Zhao, Yong 1965- (Corwin impact leadership series, 2018)
This Impact Series book by Yong Zhao is This book is about teaching for greatness. Chapter One discusses why education has been led to ignoring passion and strengths. Chapter Two makes the argument, based on current understanding of human abilities, that every child can be great. It also brings research from different disciplines to show where strengths and passions can be found. In Chapter Three, I discuss the human need for becoming great in order to achieve peace with themselves and arrive at authentic happiness. Chapter Four argues that in order to teach for greatness, we need to make education personalizable. Differing from personalized learning fundamentally, Personalizable Education gives students the control over their own learning. Features of Personalizable Education are also discussed. In the last chapter, Chapter Five, I discuss what is needed to realize Personalizable Education for all children. The author decries the standardization of curriculum and over-reliance on closing the Achievement Gap as futile and counterproductive. His examples and stories throughout the book describe practices that have gone awry and, more importantly, that have worked especially with disadvantaged children. He notes" I was lucky, on two fronts. First, I was lucky that my parents or schools did not force me to fix my weaknesses according to whatever their definitions of strengths or weaknesses. They were very forgiving of my weaknesses and appreciative of my various adventures. Second I was lucky that the massive societal transformations in China and the world over the past few decades made it possible for me to use my strengths and interests, just as the fog on Christmas Eve made it possible for Rudolph to change his fate." The fundamental reason for people to worry about the achievement gaps stems from two assumptions underlying education today [...].